2004
DOI: 10.2134/agronj2004.0247
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Herbicide-Resistant Corn Technology in a Kura Clover Living Mulch System

Abstract: and Moody, 1976). Also, when legumes are used as a living mulch, they can supply N to the main crop (Scott Previous research has shown that with adequate suppression, kura et al., 1987). clover (Trifolium ambiguum M. Bieb.) can be managed as a living mulch in corn (Zea mays L.); however, significant yield loss was Corn production in living mulch and interseeded sysobserved in some environments. This study evaluated two herbicide-tems typically results in yield loss in the North-Central resistant corn hybrids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
56
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 13 publications
4
56
2
Order By: Relevance
“…Reduced inorganic soil N in the LM cover crop system may be due to less total N applied, competition from intercropped clover for NO 3 -N, and reduced mineralization of clover residue. Other studies found similar grain yield reductions in living mulch systems and also concluded that early season competition between clover and corn was a mechanism for yield reductions (Scott et al, 1987;Echtenkamp and Moomaw, 1989;Zemenchik et al, 2000;Affeldt et al, 2004). A similar N uptake response in this study was noted in 2016, except differences in N uptake occurred earlier in the growing season and just after the V6 stage of corn development.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Reduced inorganic soil N in the LM cover crop system may be due to less total N applied, competition from intercropped clover for NO 3 -N, and reduced mineralization of clover residue. Other studies found similar grain yield reductions in living mulch systems and also concluded that early season competition between clover and corn was a mechanism for yield reductions (Scott et al, 1987;Echtenkamp and Moomaw, 1989;Zemenchik et al, 2000;Affeldt et al, 2004). A similar N uptake response in this study was noted in 2016, except differences in N uptake occurred earlier in the growing season and just after the V6 stage of corn development.…”
Section: Discussionsupporting
confidence: 82%
“…Periods of corn water stress were evident when demand from other research efforts resulted in limited opportunities for irrigation application. Regardless, mean N uptake and grain yields in this study (Table 2) were similar to N treatments in the kura clover system (Zemenchik et al, 2000;Affeldt et al, 2004).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In our case, increasing the abundance of natural enemies through the addition of a living mulch resulted in subeconomic A. glycines populations. Living mulches have been used in annual crop production with limited competition to the main crop (Affeldt et al 2004). We found evidence for signiÞcant competition between soybean and alfalfa, resulting in a yield reduction of Ϸ26% (N.P.S., unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…When compared with conventional production methods, a legume living mulch can fix enough nitrogen to reduce fertilizer requirements and increase yields in the main crop (Ilnicki and Enache 1992). However, living mulches may need to be suppressed to reduce competition with the main crop when water and nutrients are scarce (Echtenkamp and Moomaw 1989, Tharp and Kells 2001, Affeldt et al 2004. Because living mulches reduce agricultural disturbances and increase vegetational diversity, changes in the community structure of arthropod pests and their natural enemies are likely (Andow 1991).…”
mentioning
confidence: 99%